The Role of Physisorption and Chemisorption in the Oscillatory Adsorption of Organosilanes on Aluminium Oxide - Sims RA; Harmer SL; Quinton JS (MDPI (Basel, Switzerland), 2019)
The effect of physisorbed and chemisorbed species on the time-dependent self-assembly mechanism of organosilane films has been investigated on aluminium oxide using X-ray Photoelectron Spectroscopy. The role of physisorbed species was determined through their removal using a simple rinsing procedure while monitoring film substrate coverage. Removing physisorbed species from Propyldimethylmethoxysilane films, shown to follow a Langmuir-type adsorption profile, reduces the substrate coverage initially but quickly results in coverages equivalent to films that did not undergo a rinsing procedure. This indicates that all Propyldimethylmethoxysilane molecules are covalently bound to the substrate following 15 s of film growth. Removing physisorbed species from films, which have been shown to follow an oscillatory adsorption profile, Propyltrimethoxysilane and Propylmethyldimethoxysilane, reveal the persistence of these oscillations despite a reduction in silane substrate coverage. These results not only confirm the presence of two thermodynamically favourable phases in the condensation equilibrium reaction as physisorbed and chemisorbed species, but also indicate that the desorption of species during film growth involves both states of chemical binding.
Keywords: chemisorption; organosilane; oscillatory adsorption; physisorption; self-assembly